ANALISIS DAYA SAING USAHATANI KACANG TANAH DI DESA ULUGALUNG KECAMATAN EREMERASA KABUPATEN BANTAENG - Ramadani, Riska Tri; Natsir, Mohammad; Mudatsir, Rasdiana (Institute of Computer Science (IOCS), 2024)
The purpose of this study was to determine the competitiveness of peanut farming in terms of comparative advantage and competitive advantage in Ulugalung Village, Eremerasa Subdistrict, Bantaeng Regency. Sampling was done purposively from the total population of groundnut farmers in Ulugalung Village of 250 farmers, then using the Slovin formula with a margin of error of 15%, a total sample of 30 samples was obtained. Data were collected using interview, observation, documentation and recording techniques using a prepared questionnaire. The results of this study indicate that peanut farming in Ulugalung Village, Eremerasa Subdistrict, Bantaeng Regency has competitive advantage and comparative advantage. Peanut farming in Ulugalung Village, Eremerasa Subdistrict, Bantaeng Regency has a PCR value of 0.03 with a PCR value of more than <1 indicating that peanut farming has a competitive advantage that shows the efficiency of its domestic resources at actual prices. Peanut farming in Ulugalung Village, Eremerasa Subdistrict, Bantaeng Regency has a DRC value of 0.02 with a DRC value of more than <1 indicating that peanut farming has a comparative advantage that shows the efficiency of its domestic resources at international prices and is able to compete at both the village and sub-district levels.